2014
DOI: 10.3389/fncel.2014.00091
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic synapses: their plasticity and role in sensory cortex - See more at: http://journal.frontiersin.org/Journal/10.3389/fncel.2014.00091/abstract#sthash.l5jGe6MC.dpuf

Abstract: The mammalian neocortex is composed of a variety of cell types organized in a highly interconnected circuit. GABAergic neurons account for only about 20% of cortical neurons. However, they show widespread connectivity and a high degree of diversity in morphology, location, electrophysiological properties and gene expression. In addition, distinct populations of inhibitory neurons have different sensory response properties, capacities for plasticity and sensitivities to changes in sensory experience. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 322 publications
(599 reference statements)
3
26
0
Order By: Relevance
“…We have shown that in particular, the combination of plastic inhibitory feedback and plastic feed-forward inhibition has an influence on shaping the receptive fields. This is in line with recent physiological findings that inhibitory plasticity influences the mode of operation of excitatory neurons (for example the excitability) (Griffen & Maffei, 2014; Wang & Maffei, 2014; Khan et al, 2018; Znamenskiy et al, 2018), or influences the occurrence of LTP and LTD (Paille et al, 2013; Griffen & Maffei, 2014; Mongillo & Loewenstein, 2018). Previous models based on STDP rules, which have demonstrated the emergence of V1 simple cells, made several simplifications in terms of the learning dynamics (Savin et al, 2010; Zylberberg et al, 2011; King et al, 2013), or consider plasticity only for a subset of projections (Sadeh et al, 2015; Miconi et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that in particular, the combination of plastic inhibitory feedback and plastic feed-forward inhibition has an influence on shaping the receptive fields. This is in line with recent physiological findings that inhibitory plasticity influences the mode of operation of excitatory neurons (for example the excitability) (Griffen & Maffei, 2014; Wang & Maffei, 2014; Khan et al, 2018; Znamenskiy et al, 2018), or influences the occurrence of LTP and LTD (Paille et al, 2013; Griffen & Maffei, 2014; Mongillo & Loewenstein, 2018). Previous models based on STDP rules, which have demonstrated the emergence of V1 simple cells, made several simplifications in terms of the learning dynamics (Savin et al, 2010; Zylberberg et al, 2011; King et al, 2013), or consider plasticity only for a subset of projections (Sadeh et al, 2015; Miconi et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Like the glutamatergic system, the GABAergic network in the cortex is in flux for several weeks after birth (Ben-Ari et al 2004, 2012; Ciceri et al 2013; Espinosa and Stryker 2012; Gelman and Marin 2010; Griffen and Maffei 2014), resulting in a gradual increase in inhibitory strength (Chattopadhyaya et al 2004; Li et al 2012; Maffei and Turrigiano 2008). At the synaptic level, much emphasis has been placed on the documentation of changes in GABA receptor subunit expression, which vary over time by brain region and even cell type, and contribute to the maturation of inhibitory synapses (Ben-Ari et al 1994, 2012; Bosman et al 2002; Davis et al 2000; Fritschy et al 1994; Heinen et al 2004; Hensch 2005; Hornung and Fritschy 1996; Huang 2009; Laurie et al 1992; Maffei and Turrigiano 2008; Mohler 2006; Peden et al 2008; Takesian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Postnatally, changes in VGluT and VGAT expression levels are correlated with the onset of sensory experience (e.g., eye opening), and can be modified by altering sensory experience (Boulland and Chaudhry 2012; Boulland et al 2004; Chattopadhyaya et al 2004; De Gois et al 2005; Liguz-Lecznar and Skangiel-Kramska 2007; Minelli et al 2003a, b; Nakamura et al 2005; Takayama and Inoue 2010). Accordingly, these transporters are thought to play an important role in the plastic changes that shape critical period formation (Griffen and Maffei 2014; Hensch 2005; Kotak et al 2008; Kuhlman et al 2013; Lefort et al 2013; Levelt and Hubener 2012; Maffei and Turrigiano 2008; Nahmani and Turrigiano 2014; Wang and Maffei 2014). …”
Section: Introductionmentioning
confidence: 99%
“…: (1) changes in glutamatergic drive onto local inhibitory interneurons; (2) modulation of long-range inhibitory projections innervating local inhibitory neurons; or (3) neuromodulators activating local inhibitory neurons, which in turn inhibit local interneurons projecting onto principal neurons (for a comprehensive review, see Letzkus et al, 2015; see also Griffen and Maffei, 2014; Caroni, 2015; Froemke, 2015). From a clinical point of view, these findings make local disinhibitory networks attractive targets for therapeutic intervention, considering that alterations in inhibitory synaptic plasticity and excitation/inhibition-balance have been linked to behavioral and cognitive dysfunction in various brain diseases (Steinberg et al, 2015), such as schizophrenia (Yizhar et al, 2011; Rowland et al, 2013), autism (Rubenstein and Merzenich, 2003; Rojas et al, 2014) or panic disorders (Long et al, 2013).…”
Section: Role Of Disinhibitory Network In Behavioral Learningmentioning
confidence: 99%